Interactions of Cannabis sativa-derived resin with Natural Membranes: A Langmuir Films and Fluorescence Analysis - Clop, Eduardo Matias (2023)
The proposed molecule with therapeutic effects in C. sativa oils, cannabidiol (CBD), interacts with the CB1 receptor and modulates its activity, although it has been proposed that its interaction is more complex and less direct than that of tetrahidrocannabinol (THC). CBD has been observed to interact with the serotonin 5-HT1A receptor, influence GABAergic signaling and modulate the activity of enzymes and transporters. Given that CBD is a lipophilic compound, the study of non-receptor mediated interaction with biological membranes could contribute to the understanding of its mechanism of action.This research focused on analyzing the effect of a CBD-rich resin (CBD=92%, THC= 4%) on membrane models, with different degrees of complexity, by means of Langmuir films (LF) and fluorescence spectroscopy. LF were built from purified membranes of bovine brain synaptosomes (SM), as well as their lipid fraction (LF) and pure POPC phospholipids. Compression isotherms surface pressure () vs area, in the presence and absence of the resin (R) were performed for the three model membranes. Penetration experiments of R from the subphase were also performed to determine the maximum insertion pressure (MIP) of R and the association binding constant (Kb=ka/kd).The results revealed differences in the affinity of the resin for the different membrane systems, with KbPOPC﹥KbFL﹥KbSM. Moreover, MIP values showed the same tendency (POPC= 46 mN/m; FL= 43.3 mN/m y MS= 33.1 mN/m). Regarding the isotherms, it was observed that R did not significantly affect their stability and compressibility. Finally, R induced an increase in DPH, TMA-DPH fluorescence intensity, suggesting an increase in probe membrane partitioning. The decrease in the SM generalized polarization parameter of Laurdan values (from 0.63 to 0.52) in the presence of R, indicates higher dipolar relaxation and lower molecular order.In conclusion, our study provides evidence for the interaction of R with purified membranes and shows that lipid films used to mimic SM, which contain only lipid components, exhibit a different behavior when interacting with the compound especially when the kinetics of the binding behavior was analyzed.